(untitled) (Advancements in Homeopathic Research, 2022)
Background -Warts or verruca vulgaris is a viral infection caused by Human Papilloma Virus (HPV). It causes frustration to both clinician and patient due to its recurrence after cauterization . In such cases homoeopathic medicines are always beneficial when given after individualization and selection of the similimum. Method - Individualized homoeopathic medicine was given with the help of repertory.Result & Conclusion A 20 year old male patient was complaining of warts on forehead for 4 months. After getting his totality he was prescribed causticum 200 single dose and on rubrum for 15 day during follow up large warts had vanished and no new warts were observed in subsequent visits. So it is classical example of homoeopathic medicine in treatment of warts with photographical evidence. Result & Conclusion -A 20 year old male patient was complaining of warts on forehead for 4 months. After getting his totality he was prescribed causticum 200 single dose and on rubrum for 15 day during follow up large warts had vanished and no new warts were observed in subsequent visits. So it is classical example of homoeopathic medicine in treatment of warts with photographical evidence.